2019
DOI: 10.1108/ijlls-06-2019-0054
|View full text |Cite
|
Sign up to set email alerts
|

Student voice in Lesson Study as a space for EFL teachers’ learning: a case study in Kazakhstan

Abstract: Purpose The purpose of this paper is to report the findings from a case study of an action research project in the context of a secondary school in Kazakhstan where, for the first time in their teaching practice, three English as a Foreign Language teachers introduced student voice (Flutter and Rudduck, 2004) into their practice within the Lesson Study (LS) framework. The research aimed at conceptualizing Student Voice Space in LS as one of the valuable factors capable of triggering situations of disjuncture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…This finding led the authors to propose a participatory approach to LS as a vehicle to provide new insights to the complex nature and process of learning involving the students. In the study conducted by Khokhotva and Albizuri (2020), teachers are also informed on how and what students need to learn through the voice of students, which brings significant implications to teachers´ transformative learning, educational beliefs change and improvements in the lesson design.…”
Section: Dicussionmentioning
confidence: 99%
“…This finding led the authors to propose a participatory approach to LS as a vehicle to provide new insights to the complex nature and process of learning involving the students. In the study conducted by Khokhotva and Albizuri (2020), teachers are also informed on how and what students need to learn through the voice of students, which brings significant implications to teachers´ transformative learning, educational beliefs change and improvements in the lesson design.…”
Section: Dicussionmentioning
confidence: 99%
“…The findings here can be of use to these researchers in that it is demonstrated that these consultations are taking place elsewhere and that student voice is becoming more active globally. This research will, however, resonate far more with scholars in countries that do not have a strong tradition or history of student voice, such as the post-Soviet nations (Khokhotva and Albizuri 2020), but even in countries where student voice is far more pronounced and embedded questions are raised about how voice might differ between different school types and schools in different socioeconomic settings. One recent study on student participation in post-primary schools in New South Wales in Australia reported that variations between schools appeared to be more 'dependent upon the approach of the principal and/or individual teachers' than factors related to ethos/sector, demography or geography (Graham et al 2018(Graham et al , 1034) but further research is needed.…”
Section: Discussionmentioning
confidence: 84%
“…Only a few articles (13%) explained the rationale behind the means of data collection or provided additional information about the process. Articles that did include this information described, for instance, that LS groups developed their own observation forms or rubrics (e.g., Bruce et al, 2016;Craney et al, 2020), or referenced existing templates or material from a specific LS handbook (e.g., Lucenario et al, 2016;Khokhotva and Elexpuru Albizuri, 2019). A list of all articles rated with 2 for this category and their approaches to data collection can be found in the Supplementary Table S7.…”
Section: Means Of Data Collectionmentioning
confidence: 99%